2007
DOI: 10.3174/ajnr.a0848
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Aneurysms by 64-Section Multidetector CT Angiography in Patients Acutely Suspected of Having an Intracranial Aneurysm and Comparison with Digital Subtraction and 3D Rotational Angiography

Abstract: BACKGROUND AND PURPOSE: Four-section multisection CT angiography (MSCTA) accurately detects aneurysms at or more than 4 mm but is less accurate for those less than 4 mm. Our purpose was to determine the accuracy of 64-section MSCTA (64MSCTA) in aneurysm detection versus combined digital subtraction angiography (DSA) and 3D rotational angiography (3DRA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
110
1
6

Year Published

2011
2011
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 215 publications
(124 citation statements)
references
References 24 publications
7
110
1
6
Order By: Relevance
“…31,32 Interobserver agreement in our study was somewhat higher than that reported previously. 11,17,19,26 Intraobserver agreement was excellent as in another study by Lu et al 11 We had excellent interreader agreement for aneurysm identification and configuration. Our results are in line with those in other studies, 17,26 even with a recent study with 320 -detector row BSCTA 33 comparing CTA with intraoperative observations.…”
Section: Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…31,32 Interobserver agreement in our study was somewhat higher than that reported previously. 11,17,19,26 Intraobserver agreement was excellent as in another study by Lu et al 11 We had excellent interreader agreement for aneurysm identification and configuration. Our results are in line with those in other studies, 17,26 even with a recent study with 320 -detector row BSCTA 33 comparing CTA with intraoperative observations.…”
Section: Discussionsupporting
confidence: 51%
“…25 False-positive cases on both 16 -and 64 -detector row BSCTA can be explained a by focal venous plexus overlying the MCA. 17 Venous contrast has been described as a potential source of error. 26,27 Venous enhancement is, however, not a crucial factor in the detection of cerebral aneurysms, except for extensive en- The colored rectangular boxes highlight manual measurements with interpolation of DSA results because DSA millimeter calibrations were not transferred with the other DSA data.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations